Cerebral responses to pain in patients with atypical facial pain measured by positron emission tomography. Issue 10 (October 1994) - Derbyshire, S W; Jones, A K; Devani, P; Friston, K J; Feinmann, C; Harris, M; Pearce, S; Watson, J D; Frackowiak, R S
Abstract : The localised PET cerebral correlates of the painful experience in the normal human brain have previously been demonstrated. This study examined whether these responses are different in patients with chronic atypical facial pain. The regional cerebral responses to non-painful and painful thermal stimuli in six female patients with atypical facial pain and six matched female controls were studied by taking serial measurements of regional blood flow by PET. Both groups displayed highly significant differences in responses to painful heat compared with non-painful heat in the thalamus, anterior cingulate cortex (area 24), lentiform nucleus, insula, and prefrontal cortex. These structures are closely related to the "medial pain system". The atypical facial pain group had increased blood flow in the anterior cingulate cortex and decreased blood flow in the prefrontal cortex. These findings show the importance of the anterior cingulate cortex and the reciprocal (possibly inhibitory) connections with the prefrontal cortex in the processing of pain in patients with this disorder. A hypothesis is proposed to explain the mechanisms of cognitive and pharmacological manipulation of these pain processes.